Analysis of technical efficiency’s lettuce farmers in Dalat City, Vietnam - Hồ, Thị Thu Hòa (Đại học mở Thành phố Hồ Chí Minh, 2024)
The study aims to determine the technical efficiency and factors affecting the technical efficiency of lettuce farmers in Dalat City. The study’s primary data were collected by surveying structured questionnaires from 100 lettuce farmers in Dalat City. The Cobb-Douglas production, combined with the technical inefficiency according to the one-stage estimation method, was estimated by the program Frontier 4.1. The calculated results illustrate that the average technical efficiency of lettuce farmers is 0.76; with the usage level of available inputs and present techniques, Dalat lettuce production in the rainy season may increase by 24%. Besides, the study has also indicated that factors such as lettuce cultivated area, number of seedlings, and amount of pure potassium fertilizer positively influence lettuce yield. In contrast, the amount of pure nitrogen fertilizer negatively affected lettuce output. However, the education level and experience of household heads in lettuce cultivation positively affected technical efficiency. Therefore, to improve lettuce productivity and technical efficiency in Dalat City, the study suggests that farmers need to increase the amount of potassium fertilizer and reduce nitrogen fertilizer. In addition, state agencies recommend teaching lettuce farmers about the balanced and reasonable application of N, P, and K fertilizers through documents or training courses.